Design and Real-Time Implementation of Robust Permanent Magnet Synchronous Motor Control System - Huynh, Van Van; Tran, Lam The Thinh; Vu, Phan Tu (Journal of Technical Education Science, 2025)
This article examines the design of an Interior Permanent Magnet Synchronous Motor (IPMSM) control system, beginning with a study of IPMSM structure and mathematical modeling, which is vital for accurate control system. Control strategies, particularly vector control, and drive method like space vector modulation, are explored and designed. The core contribution is a maximum torque per ampere-based controller for the IPMSM, designed to optimize torque and efficiency. The article validates the controller’s performance through MATLAB Simulink simulations and real time hardware in the loop (HIL) experiments using the GatherTech HIL, bridging simulation and real-world testing. Simulation results for both non-maximum torque per ampere (N-MTPA) and maximum torque per ampere (MTPA) strategies are analyzed, demonstrating the proposed controller's performance. Results show improved torque and speed response compared to N-MTPA strategies, indicating faster acceleration, robust stabilization and enhanced the efficiency. This research provides a framework for high-performance IPMSM controllers.